2020
DOI: 10.3389/fneur.2020.00952
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Brain Function and Structure After Self-Administered Home Photobiomodulation Treatment in a Concussion Case

Abstract: Traumatic brain injury (TBI) is a common neurological disorder among athletes. Although there are no widely accepted treatments for TBI, new investigational approaches, such as photobiomodulation (PBM), are being tested. PBM is a light therapy that uses red to near-infrared (NIR) light to stimulate, heal, and protect tissue that has been injured or is at risk of dying. Benefits following transcranial PBM treatments in animal models of acute TBI and a small number of chronic TBI patients have been reported. How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(60 citation statements)
references
References 87 publications
0
60
0
Order By: Relevance
“…A similar study with ten adult patients classified with severe TBI who received PBM therapy three times a week for 6 weeks revealed increased cerebral blood flow and improved hemodynamic response (Carneiro et al, 2019). Additional similar published studies further provide evidence of the beneficial effect of PBM therapy in chronic TBI (Nawashiro et al, 2012;Hipskind et al, 2018;Chao et al, 2020).…”
Section: Mechanism Of Action Of Transcranial Near-infrared Light Brai...mentioning
confidence: 66%
“…A similar study with ten adult patients classified with severe TBI who received PBM therapy three times a week for 6 weeks revealed increased cerebral blood flow and improved hemodynamic response (Carneiro et al, 2019). Additional similar published studies further provide evidence of the beneficial effect of PBM therapy in chronic TBI (Nawashiro et al, 2012;Hipskind et al, 2018;Chao et al, 2020).…”
Section: Mechanism Of Action Of Transcranial Near-infrared Light Brai...mentioning
confidence: 66%
“…Although small, the observed improvements following Real tPBM could have been associated with decreased inflammation ( 29 ), increased focal rCBF ( 45 , 46 ), improved functional connectivity ( 51 , 55 , 57 59 ), as well as increased ATP production in hypoxic/stressed cells ( 26 ), all factors associated with PBM application.…”
Section: Discussionmentioning
confidence: 99%
“…The dementia patients were treated at home, using a NIR LED device designed to treat only the cortical node areas of the DMN. Case studies have shown improved functional connectivity in the DMN in chronic stroke/aphasia, along with improved language following a series of tLED treatments ( 55 ); likewise, improved cognition and functional connectivity in athletes with repetitive head impacts who may develop chronic traumatic encephalopathy (CTE) – e.g., pro-football ( 51 , 58 ), and ice hockey ( 59 ).…”
Section: Introductionmentioning
confidence: 99%
“…The 10 Hz pulse frequency delivered by the Neuro Alpha has been investigated and demonstrated efficacy for studies in dementia ( 29 ) and traumatic brain injury ( 40 ). This gives us cause to investigate the 10 Hz effect on structures of brain cells, particularly tubulin and microtubules, in search of further understanding of the mechanisms.…”
Section: Experimental Device Informationmentioning
confidence: 99%